2021
DOI: 10.3389/fgwh.2021.767467
|View full text |Cite
|
Sign up to set email alerts
|

The Prolactin Family of Hormones as Regulators of Maternal Mood and Behavior

Abstract: Transition into motherhood involves profound physiological and behavioral adaptations that ensure the healthy development of offspring while maintaining maternal health. Dynamic fluctuations in key hormones during pregnancy and lactation induce these maternal adaptations by acting on neural circuits in the brain. Amongst these hormonal changes, lactogenic hormones (e.g., prolactin and its pregnancy-specific homolog, placental lactogen) are important regulators of these processes, and their receptors are locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 216 publications
(269 reference statements)
1
10
0
1
Order By: Relevance
“…Prolactin has a major role in lactogenesis, increased prolactin secretion being essential for successful breastfeeding [ 42 ]. This increase in mean prolactin levels is in accordance with studies that showed that prolactin production can be increased through stimulation of the chest area or by avoiding stress and anxiety [ 10 , 43 ]. In this study, yoga practice was a mind–body–soul exercise based on breathing exercises (pranayama), physical postures (asana), and relaxation, focused on the area around the chest and breasts on the basis of complete respiration.…”
Section: Discussionsupporting
confidence: 90%
“…Prolactin has a major role in lactogenesis, increased prolactin secretion being essential for successful breastfeeding [ 42 ]. This increase in mean prolactin levels is in accordance with studies that showed that prolactin production can be increased through stimulation of the chest area or by avoiding stress and anxiety [ 10 , 43 ]. In this study, yoga practice was a mind–body–soul exercise based on breathing exercises (pranayama), physical postures (asana), and relaxation, focused on the area around the chest and breasts on the basis of complete respiration.…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown in rats that shortly prior to parturition, prolactin levels rise and during lactation, suckling induces prolactin secretion to promote milk production. Prlr activation during pregnancy has been proposed to modulate many functions, including metabolic regulation, 18 behavioural modulation [19][20][21] and glucose regulation, 22,23 to adapt the body to the state of pregnancy and prepare for the demands of lactation. 24 For example, we have previously shown that Prlr activity in the medial preoptic area (MPOA) is critical for the onset of nursing behaviour in postpartum mice.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy is associated with a plethora of changes that serve to safeguard the healthy development of the offspring. For example, physiological adaptations include food intake and energy expenditure alterations to meet the increasing metabolic demand of the growing foetus while behavioural changes occur to nurture and protect the young 1,2 . The unconscious physiological processes that are usually considered under the control of the autonomic nervous system are also dramatically altered during pregnancy, and these changes contribute to healthy foetal growth and aiding safe delivery of the offspring.…”
Section: Introductionmentioning
confidence: 99%